Physician and patient-related factors associated with inappropriate prescribing to older patients within primary care: a cross-sectional study in Brazil - Amorim, Welma Wildes; Passos, Luiz Carlos; Gama, Romana Santos; Souza, Renato Morais; Graia, Lucas Teixeira; Macedo, Jéssica Caline; Santos, Djanilson Barbosa; Oliveira, Marcio Galvão (São Paulo Medical Journal, 2021)
BACKGROUND: Physician and patient-related characteristics can influence prescription of medicationsto older patients within primary healthcare. Use of Brazilian criteria may indicate the real prevalence of prescription of potentially inappropriate medications to this population. OBJECTIVES: To evaluate prescription of potentially inappropriate medications to older patients within primary care and identify patient-related and prescribing physician-related factors. DESIGN AND SETTING: This cross-sectional study was conducted in 22 public primary care facilities in Brazil, among older people (≥ 60 years) who were waiting for medical consultations. METHODS: Interviews were conducted before and after the medical consultations. If the patient received a medical prescription at the consultation, all the drugs prescribed and the physician’s medical council registration number were recorded. Prevalence ratios were estimated to ascertain the magnitude of prescription of potentially inappropriate medications, along with patient and physician-related factors associated with such prescription. RESULTS: In total, 417 older patients were included; 45.3% had received ≥ 1 potentially inappropriate medication, and 86.8% out of 53 physicians involved had prescribed ≥ 1 potentially inappropriate medication. The strongest patient-related factor associated with higher prevalence of prescription of potentially inappropriate medications was polypharmacy. Among physician-related factors, the number of patients attended, number of prescriptions and length of medical practice < 10 years were positively associated with prescription of potentially inappropriate medications. CONCLUSIONS: High prevalence of prescription of potentially inappropriate medications was observed. Physician-related characteristics can influence prescription of medications to older people within primary healthcare. This suggests that there is a need for interventions among all physicians, especially younger physicians.